2011
DOI: 10.3354/meps09285
|View full text |Cite
|
Sign up to set email alerts
|

Coral responses to macroalgal reduction and fisheries closure on Caribbean patch reefs

Abstract: To determine the effects of algal reduction and fisheries closure, a crossed experimental design was undertaken over a 516 d period on the remote patch reefs of Glover's Reef Atoll, Belize. We investigated (1) the effects on health, growth, and survivorship of 2 transplanted coral species, Porites asteroides and Siderastrea siderea, and (2) the changes in the benthic and fish communities. Algal reduction (98% reduction by physical removal kept low by monthly removal) increased the abundance of all fish and sli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…The recovery of herbivores in fisheries closures may have lasting effects on coral reef functioning by influencing algal succession (Hoey & Bellwood 2011, McClanahan et al 2011b. Our data show that largebodied parrotfishes are vital in preventing dominance by un palatable macroalgae where fishing is prohibited.…”
Section: Discussionmentioning
confidence: 85%
“…The recovery of herbivores in fisheries closures may have lasting effects on coral reef functioning by influencing algal succession (Hoey & Bellwood 2011, McClanahan et al 2011b. Our data show that largebodied parrotfishes are vital in preventing dominance by un palatable macroalgae where fishing is prohibited.…”
Section: Discussionmentioning
confidence: 85%
“…Increased herbivory can rapidly reduce macroalgae cover (Hughes et al ., ; Stockwell et al ., ) and, in turn, increase hard‐coral cover and drive changes in benthic communities (e.g. Australia: Hughes et al ., ; Mumby and Harborne, ; Panama and Fiji: Rasher and Hay, ; Caribbean: Olds et al ., ) (but see Stockwell et al ., ; McClanahan et al ., ; and Rasher et al ., ). Protection is expected to be particularly beneficial on reefs where both mechanisms occur.…”
Section: Introductionmentioning
confidence: 94%
“…Finally, scrapping turf and fleshy macroalgae for 10–12 days from the edge of M. annularis tissue restored hyperoxia [17]. Nonetheless, two studies [28], [29] reported that some coral species did not display positive responses (in terms of coverage, growth, fecundity and mortality) to the removal of algae.…”
Section: Discussionmentioning
confidence: 97%